Comparative Evaluation of Effectiveness of Curry-leaf Mouthwash, Cinnamon Mouthwash, and Chlorhexidine Mouthwash in Maintaining Salivary and Tongue pH - Ankita Gupta; Ami Rawal (Journal of Orofacial Research, 2021)
Background & Aim: Saliva plays a critical role in maintaining oral health through various defensive mechanisms and salivary pH is a fair indicator of various dental diseases. The purpose of the study was to compare the effectiveness of curry leaf and cinnamon mouthwashes in maintaining salivary and tongue pH as compared to chlorhexidine mouthwash. Methodology: A randomized parallel-group study was conducted among 60 participants who were randomly allocated to the three groups (curry leaf, cinnamon, and chlorhexidine).The participants were asked to rinse their mouth with respective mouthwashes. Stimulated saliva was collected before and after rinsing with respective mouthwashes and the salivary and tongue coating pH were measured by a digital pH meter and coloured pH indicators. Data were analyzed statistically using one way ANOVA and Student t-test. Results: There was no statistically significant difference between the three groups in relation to salivary and tongue pH (p>0.05). Within the cinnamon mouthwash group, the mean salivary pH was only found significant between baseline and 30 minutes after rinsing (p<0.05), whereas, it was found significant at all the point intervals (p<0.05) within the curry leaf and chlorhexidine mouthwash groups. The mean tongue pH difference was found significant only between baseline and immediately after rinsing and between baseline and half an hour after rinsing with the curry leaf mouthwash (p<0.05) and non-significant within cinnamon and chlorhexidine mouthwash groups. Conclusion: Curry leaf and cinnamon mouthwashes can be considered as safe, effective, and economical agent and as an alternative to the commercially available mouthwash.